Multineutrosophic analysis of the impact of the circular economy on the regional supply chain - Ana María Correa Vaca; Fidel Márquez-Sánchez; Oscar José Alejo Machado; Cesar Pozo-Estupiñán; Orlando Arencibia-Montero (Neutrosophic Sets and Systems)
This research was conducted to evaluate the influence of the circular economy on the sustainability of supply chains at the regional level through multineutrosophic theory for uncertainty in decision-making. Empirical analysis was performed through a quantitative and qualitative assessment, including a questionnaire completed by 50 regional companies, mathematical calculations based on neutrosophic theory, and a multineutrosophic assessment of the diverse input/output resource flows for supply chains associated with manufacturing and agricultural endeavors. The major results indicate that by incorporating aspects of the circular economy, recyclability/reusability of resources was 20% more effective and 15% less expensive to operate, while 30% of the responses that could not be applied were associated with underdeveloped infrastructure; in addition, the multineutrosophic approach gives assessing and prioritizing essential chain aspects to assist in better decision-making. Ultimately, it can be determined that the circular economy generates more robust and sustainable supply chains; operational problems require supportive public policy and technological investments to solve as the subject is most effective for developing areas with fewer resources.